FINANCIAL PERFORMANCE ANALYSIS OF PT. GUDANG GARAM TBK YEAR 2023-2024 USING SOLVABILITY RATIO - Dedali, Shindu Hargo (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
We conducted this Financial Performance Research of PT. Gudang Garam Tbk to analyze the Solvency Ratio using two ratios: the Debt to Equity Ratio and the Debt to Equity Ratio, for the years 2023-2024. This research used a quantitative descriptive approach. Data for the research were obtained from the Financial Statements of PT. Gudang Garam Tbk for the years 2023-2024. The purpose of this research is to enable PT. Gudang Garam Tbk to measure its Financial Performance by analyzing two ratios: the Debt to Equity Ratio and the Debt to Equity Ratio. This allows PT. Gudang Garam Tbk to manage its debt, ensuring a smooth and effective cash flow. This also allows PT. Gudang Garam Tbk management to repay debt, enabling Gudang Garam Tbk to operate its business. Keywords: Debt to Equity Ratio, Financial Performance, & Debt to Equity Ratio